Polyester composition as well as preparation method and application thereof
By controlling the Z-average molecular weight, D-lactic acid unit content, and mineral filler particle size in the polyester composition, the problems of insufficient puncture resistance and longitudinal and transverse tear resistance of biodegradable films with high mineral fillers were solved, and the preparation of high-performance films was achieved.
Patent Information
- Application Number
- CN202411536400.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-31
AI Technical Summary
Existing biodegradable films have insufficient puncture resistance and tear resistance when the mineral filler content is high, which limits their application in scenarios where they carry sharp objects.
A polyester composition was prepared by controlling the Z-average molecular weight of biodegradable polyester, the D-lactic acid unit content of polylactic acid, and the particle size of mineral fillers, ensuring that the components are matched within a specific range to improve the puncture strength, longitudinal tear strength, and transverse tear strength of the film.
When polyester compositions are made into films with high mineral filler content, they exhibit good puncture strength, longitudinal tear strength, and transverse tear strength, meeting the requirements for lightweight and high performance.
Smart Images

Figure BDA0005111656850000091 
Figure BDA0005111656850000101 
Figure BDA0005111656850000102
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer material modification, and more specifically, to a polyester composition and a preparation method and application thereof. Background Art
[0002] Flexible polyester generally refers to a copolymer of a dibasic acid and / or its ester derivative and a diol, which has the characteristics of excellent toughness and high melt strength. Polylactic acid is a polymer obtained by polymerization of lactic acid or lactide as raw materials, which has the characteristics of bio-based source and good rigidity. Both flexible polyester and polylactic acid are biodegradable, and the combination of the two can obtain a biodegradable material that combines the advantages of both. A certain amount of mineral filler is usually added to the biodegradable material to obtain a biodegradable composite material to meet one of the main application scenarios of the biodegradable composite material: biodegradable film. The addition of mineral fillers can, on the one hand, improve the bubble stability of the biodegradable composite material when it is prepared into a film, that is, improve the processability of the film production; on the other hand, it can reduce the raw material cost of production. In order to achieve good bubble stability and control the raw material cost of production within a reasonable range, the amount of mineral filler added usually accounts for 10 to 35wt% of the biodegradable composite material.
[0003] The further promotion of biodegradable films has put forward higher requirements on their performance. Compared with traditional PE films, the puncture resistance of biodegradable films is relatively weak; and with the development of the industry, lightweight and thinning is the general trend of biodegradable films. Under this trend, the puncture resistance of biodegradable films is further weakened, which limits the application of biodegradable films in scenarios that carry certain sharp objects, such as logistics express bags, industrial product packaging bags, etc.
[0004] There are currently two ways to improve the puncture strength of biodegradable films in the industry: one is to reduce the mineral filler content of biodegradable composite materials or even use a no-filler solution, and the other is to use a multi-layer film structure. Reducing the mineral filler content of biodegradable composite materials will obviously have a negative impact on the stability of the film bubble and increase the cost of raw materials for production. The use of a multi-layer film structure places too high demands on the equipment, which is costly and reduces efficiency. Therefore, it is necessary to develop more technologies that can improve the puncture resistance of biodegradable films with high mineral filler content.
[0005] Patent CN115637023A provides a puncture-resistant biodegradable blown film. Apparently, the amount of filler added is very small, and it does not focus on the puncture resistance of the biodegradable film at a higher mineral filler content (10-35wt%).
[0006] In addition to puncture resistance, the longitudinal and transverse tearing performance of biodegradable films also needs to be paid attention to. If the longitudinal and transverse tearing performance is too low, once a gap appears in the film bag when carrying items, it is easy to further tear and damage when subjected to external force, resulting in unusable conditions. Therefore, it is necessary to improve both the puncture resistance and longitudinal and transverse tearing performance of biodegradable films. Summary of the invention
[0007] The primary purpose of the present invention is to overcome the problems of poor puncture resistance and poor longitudinal and transverse tearing properties of biodegradable films prepared from biodegradable composite materials with high mineral filler content in the current technology, and to provide a polyester composition.
[0008] A further object of the present invention is to provide a method for preparing the above polyester composition.
[0009] A further object of the present invention is to provide use of the polyester composition in preparing films.
[0010] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0011] A polyester composition comprising the following components in parts by weight:
[0012] 50-88 parts of biodegradable polyester,
[0013] 2-15 parts of polylactic acid,
[0014] 10-35 parts of mineral filler;
[0015] The biodegradable polyester is a copolymer of a dibasic acid and / or its ester-forming derivative and a diol, and the Z-average molecular weight of the biodegradable polyester is 180,000 to 400,000;
[0016] The content of D-lactic acid units in the polylactic acid is 3 to 50 mol%;
[0017] The particle size D98 of the mineral filler is ≤15 μm.
[0018] The polyester composition of the present invention comprises biodegradable polyester and polylactic acid, the combination of which gives the polyester composition basic toughness and rigidity. A certain amount of mineral filler is also added to give the polyester composition a certain rigidity and improve the processing performance of the polyester composition when it is made into a film.
[0019] The inventors of the present invention have found through research that by regulating the Z-average molecular weight of the biodegradable polyester within a specific range, the puncture strength, longitudinal tear strength and transverse tear strength of the polyester composition can be improved by entanglement of longer biodegradable polyester molecular chains. If the Z-average molecular weight is too small, it is difficult to improve each performance; if the Z-average molecular weight is too high, the fluidity of the biodegradable polyester will deteriorate, which will lead to poor compatibility with other components, thereby deteriorating the longitudinal tear strength and transverse tear strength.
[0020] The D-lactic acid unit content of polylactic acid is controlled within a suitable range, and the various properties of the polyester composition can be further improved. If the D-lactic acid unit content is too low, the crystallinity of polylactic acid is improved, and separation occurs when blended with semi-crystalline biodegradable polyester, thereby deteriorating various properties; if the D-lactic acid unit content is too high, polylactic acid will become an amorphous polymer, and will also separate from the semi-crystalline biodegradable polyester, thereby deteriorating various properties.
[0021] In addition, the particle size D98 of the mineral filler must also be controlled within a specific range to ensure that the polyester composition has good puncture strength, longitudinal tear strength and transverse tear strength.
[0022] That is, the polyester composition obtained by the present invention, through the combination of a biodegradable polyester with a specific Z-average molecular weight, polylactic acid with a specific content of D-lactic acid units and a mineral filler with a specific particle size of D98, has good puncture strength, longitudinal tear strength and transverse tear strength when made into films of different thicknesses, and it can enable the polyester composition to maintain good puncture strength, longitudinal tear strength and transverse tear strength even when it has a high content of mineral fillers.
[0023] In the present invention, biodegradable polyester is used as the main resin, and its content accounts for more than 45wt% of the polyester composition.
[0024] In the present invention, the amount of biodegradable polyester can be 50, 55, 28, 60, 62, 65, 68, 70, 75, 78, 80, 85 or 88 parts by weight; the amount of polylactic acid can be 2, 3, 5, 6, 8, 9, 10, 12 or 15 parts by weight; the amount of mineral filler can be 10, 12, 15, 18, 20, 24, 25, 28, 30, 32 or 35 parts by weight.
[0025] Preferably, the polyester composition comprises the following components in parts by weight:
[0026] 74-88 parts of biodegradable polyester,
[0027] 2-6 parts of polylactic acid,
[0028] 10-20 parts of mineral filler.
[0029] By regulating the amount of each component within this range, the puncture strength and transverse tear strength of the polyester composition are better.
[0030] In the present invention, the Z average molecular weight of the biodegradable polyester may be 180,000, 185,000, 190,000, 200,000, 240,000, 250,000, 270,000, 280,000, 300,000, 320,000, 350,000, 360,000, 380,000 or 400,000.
[0031] Preferably, the Z average molecular weight of the biodegradable polyester is 210000 to 300000. Within this range, the longitudinal tear strength and transverse tear strength of the polyester composition are better.
[0032] Preferably, the Z average molecular weight of the biodegradable polyester is 210000 to 400000. Within this range, the puncture strength of the polyester composition is better.
[0033] Biodegradable polyesters copolymerized from commonly used dibasic acids and / or their ester derivatives and commonly used diols in the art can be used in the present invention.
[0034] The biodegradable polyester of the present invention can be commercially available or homemade. The homemade method can be as follows: dibasic acid and / or its ester-forming derivatives are mixed with diol and branching agent, first reacted at 180-200° C. for 2-8 hours, a catalyst is added, and then reacted at 230-250° C. and 150-250 Pa for 8-18 hours to obtain the biodegradable polyester.
[0035] Preferably, the branching agent includes but is not limited to glycerol. The amount of the branching agent is 0.03% to 0.06% of the mass of the dibasic acid and / or its ester-forming derivative.
[0036] Preferably, the catalyst includes but is not limited to tetrabutyl titanate. The amount of the catalyst used is 0.005% to 0.015% of the total mass of the dibasic acid and / or its ester-forming derivative and the diol.
[0037] Preferably, the molar ratio of the dibasic acid and / or its ester-forming derivative to the diol is 1:(1.05-1.2).
[0038] Preferably, the dibasic acid is at least one of an aliphatic dibasic acid or an aromatic dibasic acid.
[0039] More preferably, the aliphatic dibasic acid is at least one of succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid or dodecanedioic acid.
[0040] More preferably, the aromatic dibasic acid is terephthalic acid.
[0041] More preferably, the dibasic acid is an aliphatic dibasic acid and an aromatic dibasic acid, and the molar ratio of the aromatic dibasic acid to the aliphatic dibasic acid is 1:(0.80-1.20); specifically, it can be 1:0.8, 1:0.85, 1:0.87, 1:0.90, 1:0.95, 1:1, 1:1.05, 1:1.1, 1:1.15, 1:1.16 or 1.20.
[0042] More preferably, the diol is at least one of butanediol, propylene glycol, ethylene glycol or pentanediol.
[0043] Specifically, the biodegradable polyester can be at least one of polybutylene adipate terephthalate (PBAT), polybutylene sebacate terephthalate (PBSeT), polybutylene succinate terephthalate (PBST), polybutylene sebacate adipate terephthalate (PBSeAT), polybutylene sebacate succinate terephthalate (PBSeST), polybutylene succinate adipate terephthalate (PBSAT) or polypropylene adipate terephthalate (PDAT).
[0044] Preferably, the melt index of the polylactic acid measured at 190° C. and 2.16 kg is 2 to 30 g / 10 min.
[0045] In the present invention, the melt index of polylactic acid can be measured according to ISO 1133-1:2022 standard.
[0046] In the present invention, the polylactic acid can be obtained commercially or by self-production. The self-production method can be as follows: a lactide raw material containing L-lactide and meso-lactide and / or lactic acid is added to a solvent to cause a ring-opening polymerization reaction to obtain the polylactic acid.
[0047] Preferably, a lactide raw material containing L-lactide and meso-lactide is added to a solvent to undergo a ring-opening polymerization reaction to obtain the polylactic acid.
[0048] More preferably, the mass ratio of L-lactide to meso-lactide is 1-92:8-99; further preferably, it is 1-90:10-99.
[0049] More preferably, the solvent includes but is not limited to hexylene glycol.
[0050] More preferably, the ring-opening polymerization reaction is carried out in the presence of a catalyst, and the catalyst includes but is not limited to stannous octoate.
[0051] More preferably, the process of the ring-opening polymerization reaction is: first react at 130-140° C. and 1100-1300 Pa for 3-4 hours, and then react at 160-180° C. and 250-350 Pa for 4-6 hours.
[0052] Preferably, the molecules of the polylactic acid consist of L-lactic acid units and D-lactic acid units.
[0053] In the present invention, the content of D-lactic acid units in the polylactic acid can specifically be 3, 3.5, 4, 5, 8, 10, 12, 15, 18, 20, 24, 25, 28, 30, 33, 35, 36, 38, 40, 42, 45, 48 or 50 mol%.
[0054] Preferably, the content of D-lactic acid units in the polylactic acid is 10-35 mol%. Within this range, the puncture strength, longitudinal tear strength and transverse tear strength of the polyester composition are better.
[0055] Preferably, the glass transition temperature (Tg) of the polylactic acid is ≤65°C.
[0056] More preferably, the glass transition temperature of the polylactic acid is ≤62°C.
[0057] More preferably, the glass transition temperature of the polylactic acid is ≤60°C.
[0058] Preferably, the content of mineral filler in the polyester composition is 10-35 wt %, and specifically can be 10, 12, 15, 18, 20, 24, 25, 28, 30, 32 or 35 wt %.
[0059] Preferably, the mineral filler is at least one of calcium carbonate, talc or montmorillonite.
[0060] When calcium carbonate is selected as the mineral filler, the longitudinal tear strength and the transverse tear strength of the polyester composition are better; when talc is selected as the mineral filler, the puncture strength of the polyester composition is better.
[0061] In the present invention, the particle size D98 of the mineral filler can specifically be 3, 5, 7, 8, 9, 10, 11, 12, 13, 14 or 15 μm.
[0062] Preferably, the particle size D98 of the mineral filler is: 7 μm ≤ D98 ≤ 15 μm.
[0063] Preferably, the polyester composition further comprises 0.2 to 2 parts of other auxiliary agents.
[0064] Optionally, the other auxiliary agent is at least one of an antioxidant, a UV stabilizer or a UV absorber.
[0065] Usually, the dosage of each other auxiliary agent is: 0.01-0.3 parts by weight of antioxidant, 0.05-2 parts by weight of UV absorber, and 0.1-3 parts by weight of UV stabilizer.
[0066] Optionally, the antioxidant is at least one of antioxidant 1010 or antioxidant 168.
[0067] Optionally, the UV stabilizer is at least one of bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate or 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-(2,4-dimethylphenyl)-2H-benzotriazol-4-one.
[0068] Optionally, the UV absorber is at least one of 2,4-dihydroxybenzophenone, phenyl o-hydroxybenzoate, 2-hydroxy-4-methoxybenzophenone or 2-hydroxy-4-n-octyloxybenzophenone.
[0069] The preparation method of the polyester composition comprises the following steps: mixing the components, melt-extruding, and granulating to obtain the polyester composition.
[0070] Preferably, the temperature of the melt extrusion is 160-180° C.; the screw length-to-diameter ratio of the melt extruder is 30-50:1, and the screw speed is 250-400 rpm.
[0071] The use of the above polyester composition in preparing films also falls within the protection scope of the present invention.
[0072] A film is prepared from the polyester composition.
[0073] Compared with the prior art, the present invention has the following beneficial effects:
[0074] The polyester composition obtained by the present invention, through the combination of a biodegradable polyester with a specific Z-average molecular weight, polylactic acid with a specific content of D-lactic acid units and a mineral filler with a specific particle size of D98, has good puncture strength, longitudinal tear strength and transverse tear strength when made into films of different thicknesses, and can enable the polyester composition to maintain good puncture strength, longitudinal tear strength and transverse tear strength when having a high content of mineral fillers. DETAILED DESCRIPTION
[0075] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.
[0076] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:
[0077] Biodegradable polyester 1#: homemade, PBAT, the preparation method is as follows:
[0078] 2.0 kg of terephthalic acid, 2.0 kg of adipic acid, 2.6 kg of 1,4-butanediol (excess), and 2.0 g of glycerol were added to a 20 L reactor, stirred at 190 ° C (recorded as temperature T1) for 3 hours (recorded as time t1), and then 0.01% of tetrabutyl titanate, which accounts for the total mass of the dibasic acid and diol, was added as a catalyst, and the temperature was raised to 240 ° C (recorded as temperature T2), and the vacuum was opened, the vacuum degree was 200 Pa, and the reaction was carried out for 8 hours (recorded as time t2), and the biodegradable polyester 1# was obtained. The Z average molecular weight of the biodegradable polyester 1# is 231600 Da.
[0079] Biodegradable polyester 2#: homemade, PBAT, the preparation method thereof is different from that of biodegradable polyester 1# in that the time t1 is 5 hours and the time t2 is 12 hours. The Z average molecular weight of biodegradable polyester 2# is 297800 Da.
[0080] Biodegradable polyester 3#: homemade, PBAT, the preparation method thereof is different from that of biodegradable polyester 1# in that: time t1 is 8 hours, time t2 is 18 hours. The Z average molecular weight of biodegradable polyester 3# is 398040Da.
[0081] Biodegradable polyester 4#: homemade, PBAT, the preparation method thereof is different from that of biodegradable polyester 1# in that: time t1 is 2 hours, time t2 is 14 hours. The Z average molecular weight of biodegradable polyester 4# is 187607 Da.
[0082] Biodegradable polyester 5#: homemade, PBSeT, the preparation method is different from that of biodegradable polyester 1# in that 2.0 kg of adipic acid is replaced by 3.2 kg of sebacic acid. The Z average molecular weight of biodegradable polyester 5# is 234895 Da.
[0083] Biodegradable polyester 6#: homemade, PDAT, the preparation method is different from that of biodegradable polyester 1# in that 2.6 kg of 1,4-butanediol is replaced by 2.2 kg of propylene glycol (excess). The Z average molecular weight of biodegradable polyester 6# is 225898 Da.
[0084] Biodegradable polyester 7#: homemade, PBAT, the preparation method thereof is different from that of biodegradable polyester 1# in that: time t1 is 1 hour, time t2 is 2 hours. The Z average molecular weight of biodegradable polyester 7# is 159632 Da.
[0085] Biodegradable polyester 8#: homemade, PBAT, the preparation method thereof is different from that of biodegradable polyester 1# in that: time t1 is 8 hours, time t2 is 24 hours. The Z average molecular weight of biodegradable polyester 8# is 416232 Da.
[0086] Z average molecular weight test method:
[0087] The GPC test method is: GPC uses Waters' ACQUITY APC TM The equipment was tested at 40°C, using XT45, XT200 and XT459 columns, solvent: tetrahydrofuran, mobile phase flow rate: 0.5mL / min. Polystyrene standards were used as standard samples. The results were averaged three times.
[0088] Polylactic acid 1#: homemade, the preparation method is as follows: 90 parts by weight of L-lactide (L content ≥ 99.5%, the same below) and 10 parts by weight of meso-lactide (D content is about 50%, the same below) are dissolved in hexanediol, stannous octoate is added, and ring-opening polymerization is carried out: first, the reaction temperature is 135°C and the reaction pressure is 1200Pa for 4 hours, and then the reaction temperature is 170°C and the reaction pressure is 300Pa for 6 hours; underwater pelletizing, crystallization, and drying obtain polylactic acid 1#. The D content of polylactic acid 1# is 4.9%, the glass transition temperature is 59°C, and the melt index is 4.2g / 10min.
[0089] Polylactic acid 2#: homemade, the preparation method is different from that of polylactic acid 1# in that the amount of L-lactide is 84 parts by weight, and the amount of meso-lactide is 16 parts by weight. The D content of polylactic acid 2# is 8.1%, the glass transition temperature is 55°C, and the melt index is 3.9g / 10min.
[0090] Polylactic acid 3#: homemade, the preparation method is different from that of polylactic acid 1# in that the amount of L-lactide is 30 parts by weight, and the amount of meso-lactide is 70 parts by weight. The D content of polylactic acid 3# is 34.6%, the glass transition temperature is 50°C, and the melt index is 4.1g / 10min.
[0091] Polylactic acid 4#: homemade, the preparation method is different from that of polylactic acid 1# in that the amount of L-lactide is 1 part by weight, and the amount of meso-lactide is 99 parts by weight. The D content of polylactic acid 4# is 49.8%, the glass transition temperature is 48.1°C, and the melt index is 4.0g / 10min.
[0092] Polylactic acid 5#: homemade, its preparation method is different from that of polylactic acid 1# in that it is first reacted at a reaction temperature of 135°C and a reaction pressure of 1200 Pa for 3 hours, and then reacted at a reaction temperature of 170°C and a reaction pressure of 300 Pa for 4 hours. The D content of polylactic acid 5# is 4.0%, the glass transition temperature is 60°C, and the melt index is 7.7 g / 10 min.
[0093] Polylactic acid 6#: Homemade, the preparation method is different from that of polylactic acid 1# in that the amount of L-lactide is 98 parts by weight and the amount of meso-lactide is 2 parts by weight. The D content of polylactic acid 6# is 1%, the glass transition temperature is 60.5°C, and the melt index is 4.1g / 10min.
[0094] Polylactic acid 7#: homemade, its preparation method is different from that of polylactic acid 1# in that 10 parts by weight of D-lactide (D content ≥ 99.5%) and 90 parts by weight of meso-lactide are added. The D content of polylactic acid 7# is 54.6%, the glass transition temperature is 47.0°C, and the melt index is 3.9g / 10min.
[0095] The D-type content of polylactic acid can be specifically detected according to the following steps: (1) Weigh 100±10 mg of ground polylactic acid sample and place it in a 25 mL pressurized container; (2) Add 10 mL of methanol and 1 drop of dilute sulfuric acid; (3) Seal the pressurized container and place it in a 150°C thermostat for 4 hours; (4) Take out the pressurized container and open the lid after the container cools to room temperature; (5) After the sample solution is filtered through a membrane filter (pore size 0.22 or 0.45 μm), transfer it to a gas chromatograph (Agilent 8860 gas chromatograph, CP7502 chromatographic column) and operate according to the equipment manufacturer's instructions; (6) Calculate the D-type content based on the peak area ratio.
[0096] The test method for the glass transition temperature Tg of polylactic acid is carried out on the DSC204 thermal analyzer of Netzsch Company in Germany, with nitrogen protection. A sample with a mass of 5±1 mg is first heated from 30°C to 160°C at a heating rate of 10°C / min, and maintained at 160°C for 3 minutes, then cooled to -110°C at a rate of 20°C / min, and then heated to 150°C at a rate of 10°C / min; the glass transition temperature Tg of the sample is taken from the curve of the second heating, and the intersection of the epitaxial line at the inflection point and the baseline is taken as the value of the glass transition temperature Tg.
[0097] Mineral filler 1#: calcium carbonate, Omiya, 1T-JI, D98: 7.8 μm;
[0098] Mineral filler 2#: calcium carbonate, Omiya, 2T-JI, D98: 14.3μm;
[0099] Mineral filler 3#: talcum powder, Aihai, AHCP 250, D98: 8.0 μm;
[0100] Mineral filler 4#: calcium carbonate, Omiya, 5T-JI, D98: 16.7μm;
[0101] The D98 of mineral fillers can be determined by referring to GB / T 19077.1 "Particle size analysis by laser diffraction method".
[0102] Other additives 1#: Antioxidant 168 and antioxidant 1010 in a mass ratio of 1:1. Antioxidant 168 and antioxidant 1010 are both commercially available.
[0103] Unless otherwise specified, the components (such as other auxiliary agent 1#) selected in each parallel example and comparative example are the same commercially available products.
[0104] The polyester compositions provided in the embodiments and comparative examples of the present invention were firstly respectively passed through a film blowing machine, and the feeding speed was adjusted to form films with a thickness of 30 μm and 50 μm, and then the performance was measured according to the following test method:
[0105] 1) Puncture strength: Use a film universal testing machine to test the puncture performance of the film bag. According to GB / T21302-2007, fix the film on the film universal testing machine, use a 1mm diameter puncture test needle, and test at a speed of 50mm / min, and take the maximum force value. The test value is the average of 5 times.
[0106] 2) Longitudinal tear strength: In the longitudinal direction of the film, the tearing properties of the film are tested according to GB / T 16578.2-2009.
[0107] 3) Transverse tear strength: In the transverse direction of the film, the tearing properties of the film are tested according to GB / T 16578.2-2009.
[0108] The polyester compositions of the embodiments and comparative examples of the present invention are prepared by the following preparation method:
[0109] Weigh each component according to the formula, mix the components evenly, and then put them into a twin-screw extruder for melt extrusion and granulation to obtain a polyester composition. The temperatures of the twin-screw extruder from zone 1 to zone 10 are 160°C, 170°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C, 180°C and 180°C, respectively, the aspect ratio of the screw is 40:1, and the screw speed is 300rpm.
[0110] Examples 1 to 14
[0111] Examples 1 to 14 provide a series of polyester compositions, whose formulations are shown in Tables 1 and 2.
[0112] Table 1 Formulas of Examples 1 to 8 (parts by weight)
[0113]
[0114]
[0115] Table 2 Formulas of Examples 9 to 14 (parts by weight)
[0116]
[0117] Comparative Examples 1 to 5
[0118] Comparative Examples 1 to 5 provide a series of polyester compositions, whose formulations are shown in Table 3.
[0119] Table 3 Formulas of Comparative Examples 1 to 5 (parts by weight)
[0120]
[0121]
[0122] The properties of the polyester compositions of the embodiments and comparative examples were measured according to the above-mentioned test methods. The test results are shown in Table 4.
[0123] Table 4 Performance test results of the polyester compositions of various embodiments and comparative examples
[0124]
[0125] From Table 4, we can see that:
[0126] When the polyester composition of each embodiment is made into a film with a thickness of 30 μm, the puncture strength is all above 1.1N, the longitudinal tear strength is all above 1000 mN, and the transverse tear strength is all above 1800 mN; when it is made into a film with a thickness of 50 μm, the puncture strength is all above 1.7N, the longitudinal tear strength is all above 2400 mN, and the transverse tear strength is all above 3800 mN, indicating that the polyester composition of the present invention has good puncture strength, longitudinal tear strength and transverse tear strength when made into films of different thicknesses.
[0127] The molecular weight of the biodegradable polyester added in Comparative Example 1 is too small. After the polyester composition is made into a film, the puncture strength and longitudinal tear strength are poor, and the transverse tear strength is lower than that of Example 1 and Examples 4 to 6. The molecular weight of the biodegradable polyester added in Comparative Example 2 is too large. After the polyester composition is made into a film, the puncture strength and longitudinal tear strength are poor, and the transverse tear strength is lower than that of Example 1 and Examples 4 to 6. The D content of the polylactic acid added in Comparative Example 3 is too little, and the D content of the polylactic acid added in Comparative Example 4 is too much. After the polyester composition is made into a film, the puncture strength and longitudinal tear strength are poor, and the transverse tear strength is lower than that of Example 1 and Examples 9 to 11. The particle size D98 of the mineral filler added in Comparative Example 5 is too large. After the polyester composition is made into a film, the puncture strength and longitudinal tear strength are poor, and the transverse tear strength is lower than that of Example 1 and Examples 13 to 14.
[0128] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A polyester composition, characterized in that The composition comprises the following components in parts by weight: 50-88 parts of biodegradable polyester, 2-15 parts of polylactic acid, 10-35 parts of mineral filler; The biodegradable polyester is a copolymer of a dibasic acid and / or its ester-forming derivative and a diol, and the Z-average molecular weight of the biodegradable polyester is 180,000 to 400,000; The content of D-lactic acid units in the polylactic acid is 3 to 50 mol%; The particle size D98 of the mineral filler is ≤15 μm.
2. The polyester composition according to claim 1, characterized in that: The dibasic acid is an aliphatic dibasic acid and / or an aromatic dibasic acid.
3. The polyester composition according to claim 2, characterized in that: The aliphatic dibasic acid is at least one of succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid or dodecanedioic acid; and the aromatic dibasic acid is terephthalic acid.
4. The polyester composition according to claim 1, characterized in that: The melt index of the polylactic acid measured at 190° C. and 2.16 kg is 2 to 30 g / 10 min.
5. The polyester composition according to claim 1, characterized in that: The mineral filler is at least one of calcium carbonate, talc or montmorillonite.
6. The polyester composition according to claim 1, characterized in that: The particle size D98 of the mineral filler is 5 μm ≤ D98 ≤ 15 μm.
7. The polyester composition according to claim 1, characterized in that: The glass transition temperature of the polylactic acid is ≤65°C.
8. The method for preparing the polyester composition according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing various components, melt-extruding, and granulating to obtain the polyester composition.
9. Use of the polyester composition according to any one of claims 1 to 7 in the preparation of films.
10. A film, characterized in that: The polyester composition is prepared by any one of claims 1 to 7.
Citation Information
Patent Citations
Biodegradable material and preparation method thereof
CN115403902A
Biodegradable material as well as preparation method and application thereof
CN117343505A
Biodegradable composition as well as preparation method and application thereof
CN117430930A
Polylactic acid composite material as well as preparation method and application thereof
CN117903583A
Biodegradable polyester polymer and easy-to-tear film comprising same
CN118108932A
Cited By
Biodegradable polyester material as well as preparation method and application thereof
CN120118487A
Biodegradable composition and preparation method thereof
CN120158050A
Polyester composition as well as preparation method and application thereof
CN121628317A
A polyester composition, its preparation and use
CN121628317B
Biodegradable composition as well as preparation method and application thereof
CN121673770A